Is Connectivity a Desirable Property in Urban Resilience Assessments? - Olazabal, Marta; Chelleri, Lorenzo; Sharifi, Ayyoob (Springer, 2018)
The need to look at environmental-related problems from a systemic perspective has been increasingly highlighted in current scientific literature. Especially in a context of climate change uncertainty, it is helpful to identify interdependencies and cascading impacts that might happen under certain management or policy scenarios. In the context of resilience management and given the inherent complexity of cities, this becomes especially relevant if one considers potential trade-offs or perverse transformability interventions that may have negative impacts on environmental quality, social equity or well-being. The network perspective in resilience theory has been argued to be useful to assess system’s robustness, connectivity and dependency. Connectivity as a characteristic of the system, has been particularly presented as a determinant of urban resilience in the literature, but, so far and to our knowledge, no study has presented empirical evidence on this regard. To contribute to this debate, this chapter uses a case study on urban energy resilience in the city of Bilbao (Spain) to illustrate the role of connectivity in an urban system and its positive and negative effects on resilience and transformability. Main findings point out the context-specific nature of this property of the system and the difficulty of establishing a normative desirable trend.
Keywords: Stadtentwicklung; Städtische Infrastruktur; Resilienz; Netzwerk; Energieversorgung; Nachhaltigkeit; Bebauungsdichte; Zentralität; Fallstudie; Konnektivität